Cobalt‐Catalyzed Diastereo‐ and Enantioselective Hydroalkenylation of Cyclopropenes with Alkenylboronic Acids. Issue 32 (3rd July 2019) - Zhang, Haiyan; Huang, Wei; Wang, Tongtong; Meng, Fanke
Abstract: Catalytic diastereo‐ and enantioselective hydroalkenylation of 3, 3‐disubstituted cyclopropenes with readily accessible alkenylboronic acids, promoted by a chiral phosphine/Co complex, is presented. Such a process constitutes the unprecedented and direct introduction of a wide range of alkenyl groups onto the cyclopropane motif to afford multisubstituted cyclopropanes in up to 95 % yield with greater than 95:5 d.r. and 99:1 e.r. Functionalization of the products delivered enantioenriched cyclopropanes that are otherwise difficult to access. Abstract : By way of introduction : A new method for highly efficient, diastereo‐ and enantioselective hydroalkenylation of cyclopropenes, catalyzed by a readily accessible Co complex, was developed. This protocol represents the first approach for the introduction of a wide range of alkenyl units onto a cyclopropane ring.